The effects of a pneumatic-driven variable valve timing mechanism on the performance of an Otto engine - Uysal, Fatih (Strojniški vestnik, 2015)
In this study, the classic cam mechanism of a single cylinder, four-stroke, 6 hp spark-ignited engine was replaced by an electro-pneumatic rocker mechanism, which is designed and manufactured to open the intake valve at low (3.7 mm), normal (5.7 mm) and high (7.7 mm) lifts between engine speeds of 1600 rpm to 2200 rpm. An air compressor was used to feed 6 bar air pressure in order to have the plungers drive the cams in an orderly manner. A control panel was used to control plungers in order to modulate the valve lifts gradually. The volumetric efficiency, torque, power and specific fuel consumption with this operation were measured at full load and compared to the values with a classic cam mechanism. The results of the study showed that decreasing the valve lift at low engine speeds and increasing the lift at high speeds improve the engine performance. Moreover, it was concluded that the idle speed can be lowered by decreasing the valve lift at low engine speeds.
Keywords: elektropnevmatski mehanizem nihajnih vzvodov; Ottov motor; variabilno krmiljenje ventilov; vžigalna svečka; zmogljivost motorja